1990
DOI: 10.1017/s0890037x00026609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weed Control and Irrigation on the Growth of Young Pecans

Abstract: The effect of irrigation and weed control by various mechanical and chemical means was evaluated over a 4-yr period on newly planted pecans [Carya illinoensis(Wang.) K. Koch]. Weed control effect on tree growth became evident in the second growing season, and became more pronounced after the third and fourth season. After the fourth season, the maximum increase in tree diameter (384%) was achieved with comprehensive, herbicide-based weed control. Mowing provided a 224% increase, which was equivalent to the unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
32
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 4 publications
5
32
1
Order By: Relevance
“…Vegetative groundcover surrounding trees competes for nutrients (Bould and Jarrett, 1962;Goff et al, 1991;Smith et al, 1959;Worley and Carter, 1972) and water (Patterson et al, 1990;Ware and Johnson, 1958), and in some instances may be allelopathic (Friedman and Horowitz, 1970;Meissner et al, 1989;Menges, 1987;Smith et al, 2001;Wolf and Smith, 1999). Tree growth during orchard establishment can be increased by maintaining a vegetation-free area surrounding the tree (Foshee et al, 1995;Patterson et al, 1990;Patterson and Goff, 1994;Smith et al, 2002;Wolf and Smith, 1999).…”
mentioning
confidence: 99%
“…Vegetative groundcover surrounding trees competes for nutrients (Bould and Jarrett, 1962;Goff et al, 1991;Smith et al, 1959;Worley and Carter, 1972) and water (Patterson et al, 1990;Ware and Johnson, 1958), and in some instances may be allelopathic (Friedman and Horowitz, 1970;Meissner et al, 1989;Menges, 1987;Smith et al, 2001;Wolf and Smith, 1999). Tree growth during orchard establishment can be increased by maintaining a vegetation-free area surrounding the tree (Foshee et al, 1995;Patterson et al, 1990;Patterson and Goff, 1994;Smith et al, 2002;Wolf and Smith, 1999).…”
mentioning
confidence: 99%
“…Many studies demonstrated substantial tree growth and yield reductions associated with floor vegetation of young pecan orchards in the humid southeastern United States (Faircloth et al, 2007;Foshee et al, 1995;Patterson and Goff, 1994;Patterson et al, 1988Patterson et al, , 1990Smith, 2011;Smith et al, 2002Smith et al, , 2005. In Patterson and Goff's 1994 study that examined newly planted trees for 8 consecutive years, trees subjected to total chemical vegetation control produced over five times more pecans in the last 3 years of the study than trees competing with vegetation.…”
mentioning
confidence: 99%
“…Cultural practices that promote tree growth and vigor during the establishment phase are desirable for increasing tree fruiting surface. Numerous studies have examined the effects of planting practices, fertilizer, mulching, weed competition, and irrigation on growth of young pecan trees (Conner, 2007;Foshee et al, 1996Foshee et al, , 1997Patterson et al, 1990;Smith et al, 2000Smith et al, , 2005Smith and Wolf, 2001;Wood, 1996).…”
mentioning
confidence: 99%